Penggalakkan Pelaporan Pajak di Era Digitalisasi pada Pusat Pedagang dan Servis Jam Tangan di Jakarta Pusat - Sugianto Sugianto (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
Along with the development of internet technology which is increasingly progressing very rapidly, it will increasingly encourage transformation in the business world. In addition, the development of internet technology has also modernized the economy of every country in the world. technological developments in this era of globalization, the government is always trying to improve services in terms of tax payments by modernizing the tax system. The aim of modernization is to provide better, comfortable, friendly, easy, efficient service, so that taxpayers do not think that paying taxes is a burden. This has made many parties benefit from the development of internet technology, such as: citizens, consumers, individuals, groups of people and members of a community. The purpose of this research is to promote tax reporting and management using today's digital technology and how to respond to changes in tax regulations, especially for watch dealers at the Senen watch dealer and service center, Central Jakarta. As a result of this activity, traders and watch repair businesses understand digital tax reporting technology.